Nove tehnologije in njihov vpliv na pojavnost in pregon kriminalitete - Šugman, Katja (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2013)
The article analyses the effects of certain contemporary new technologies on crime and criminal investigation, taking into account how data gathered by these technologies being deployed for preventative purposes often becomes evidence for criminal procedure. Special attention is given to measures which all potentially breach the right to privacy: measures to investigate cybercrime, measures introduced on the basis of the doctrine of special needs, roving wiretaps, data-mining and the use of so-called protective technologies. Given the greater scope such technologies provide for avoiding certain classical criminal procedure safeguards, the state must take special care to guarantee a balance of conflicting rights by providing strict judicial control of such overextended, general and preventive measures and strict exclusion of the evidence thus gathered.
Keywords: criminal law; kazensko pravo; kazniva dejanja; elektronski kriminal; tehnološki razvoj; nadzor